Development of Basic Electrical Learning Video to Improve Student’s Competencies - Eko Swi Damarwan; Pramudita Budiastuti; Adhy Kurnia Triatmaja (Journal of Vocational Education Studies, 2022)
In the digitalization era, the learning process has begun to use blended learning. Blended learning is carried out face-to-face directly or indirectly. Students are expected to be able to study independently. In basic electrical practice courses, students have difficulty learning independently. This study aims to develop learning videos to improve student competencies. The development model used is the ADDIE model. The stages of development carried out are Analyze, Design, Development, Implementation, and Evaluation. The feasibility test of the basic electrical learning video in terms of motivation is 90.29%, convenience is 88.50% and material is 86.75% The feasibility of basic electrical learning videos as learning media is included in the "very feasible" category. This learning media can be used to support the learning process of basic electrical practices.